Distribution of magnetic nanoparticles after magnetic drug targeting in an ex vivo bovine artery model - Lyer, Stefan; Tietze, Rainer; Jurgons, R.; Richter, H.; Wiekhorst, F.; Schwarz, K.; Trahms, L.; Alexiou, Christoph (IFMBE Proceedings, 2009)
The aim of Magnetic Drug Targeting (MDT) in cancer therapy is to concentrate chemotherapeutics to a tumor region while simultaneously the over all dose is reduced. This can be achieved by coated superparamagnetic nanoparticles bound to a chemotherapeutic agent. These particles are applied intraarterially close to the tumor region and focused to the tumor by a strong external magnetic field. The interaction of the particles with the field should make them accumulate in the region of the steepest field gradient. Here, we suggest an artery model by which the magnetic targeting mechanism can be studied in detail. In particular, we focus on the quantification of the accumulation profile along the artery by SQUID-based magnetorelaxometry. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Magnetic drug targeting; Magnetorelaxometry; Nanomedicine; Nanotechnology